Effect of vitamin C supplementation on outcomes in patients with COVID-19: a systematic review and meta-analysis - Xu, Wenhao; Wang, Peng; Wan, Jun; Tan, Yaheng; Liu, Yuyang; Chen, Qiwen; Zheng, Yuxin; Yu, Xueying; Fan, Sitong; Jorge Luis, Cuyubamba Dominguez; Zhang, Yu (Frontiers in Nutrition, 2024)
Background Since the emergence of the coronavirus disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), millions of lives have been lost, posing formidable challenges to healthcare systems worldwide. Our study aims to conduct a meta-analysis to evaluate the efficacy of vitamin C supplementation in reducing in-hospital mortality rates and shortening the length of ICU or hospital stays among patients diagnosed with COVID-19. Methods A comprehensive systematic review and meta-analysis was conducted, sourcing data from PubMed, Embase, Scopus, and the Cochrane Central Register of Controlled Trials. Our analysis focused on randomized clinical trials comparing the efficacy of vitamin C supplementation with standard care in adult COVID-19 patients. Results Through meticulous examination of 11 clinical trials, our meta-analysis found that vitamin C supplementation did not reduce in-hospital mortality rates in COVID-19 patients compared to those receiving standard care (Risk Ratio [RR] = 0.85; 95% Confidence Interval [CI]: 0.62–1.17; p = 0.31). Similarly, the analysis indicated no significant difference in the length of ICU stays between both cohorts. Additionally, the occurrence of other adverse events was found to be similar across both groups treated with vitamin C supplementation and standard care (all p > 0.05). Conclusion Vitamin C supplementation did not reduce in-hospital mortality or ICU stay durations in patients with COVID-19. The interpretation of these findings is limited by the small number of available studies and participants, which affects the strength of the conclusions. Clinical trial registration Identifier CRD42024497474.